CONTROL OF STATIC AND DYNAMIC MODES OF ASYNCHRONOUS MOTOR OF FODDER GRINDING DEVICES - Panoyev, Abdullo; Nurali , Nurali (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article covers the ways of achieving energy savings by controlling the speed of asynchronous electric motors in a frequency method. Frequency control is economical because it increases the efficiency and reduces power loss by adjusting the speed of the asynchronous motor.